Voting Behavior of Teachers in North Philippines and its Implication to Education - Reyes, Agnes S; Garcia, Judith R (SUSURGALUR, 2015)
ABSTRACT: The Philippines, in its form, is a democratic and a republican state with Presidential in form. Thus, with its being democratic, it is in the people where sovereignty resides. It is in their hands that people signifying intentions to occupy elected positions are to be instituted to do such. While good governance is the process by which institutions conduct the affairs of the government as they manage the resources of the public in order to guarantee the realization of human rights. The study endeavored to describe and analyze the elements that determine and influence the teachersâ decision to vote for particular candidates in the Philippine 2013 midterm election, through the use of quantitative and qualitative research methods. Survey questionnaires were administered to a sample composing twenty percent of the total number of teachers per school. The study revealed that teachersâ choice did not match with the votersâ choice in the 2013 midterm election for Senators and party list. The result posts a great challenge to education as an agent of socio-political transformation. It implies that education must help people fully understand the political condition of the country; and teachers are tasked to engage themselves seriously in shaping political consciousness and attitudes among their clients.KEY WORD: Voting Behavior; Teachers; Midterm Election; Senators and Party List; Socio-Political Transformation.Â IKHTISAR: âTindakan Pemberian Suara Guru-guru di Filipina Utara dan Implikasinya terhadap Pendidikanâ. Filipina, dalam kenyataannya, adalah negara demokratis dan republik dengan bentuk Presidensial. Dengan menjadi negara demokratis, maka kedaulatan berada di tangan rakyat. Di tangan rakyat pula mereka yang ingin menduduki posisi wakil rakyat dipilih dan harus terus dilembagakan. Sementara itu pemerintah yang baik adalah proses dimana lembaga melakukan urusan pemerintahan karena mereka mengelola sumber daya publik untuk menjamin realisasi hak asasi manusia. Studi ini berusaha untuk menggambarkan dan menganalisis unsur-unsur yang menentukan dan mempengaruhi keputusan para guru dalam memilih calon wakil mereka dalam pemilihan umum daerah di Filipina tahun 2013, melalui penggunaan metode penelitian kuantitatif dan kualitatif. Kuesioner survei diberikan kepada sampel yang terdiri atas 20% dari jumlah guru per sekolah. Hasil penelitian menunjukan bahwa pilihan guru tidak sejalan dengan pilihan masyarakat pemberi suara dalam pemilihan umum daerah tahun 2013 untuk memilih Senator dan daftar calon partai politik. Hasil kajian ini merupakan tantangan besar bagi dunia pendidikan sebagai agen transformasi sosial-politik. Ini menyiratkan bahwa pendidikan harus membantu masyarakat memahami kondisi politik negara; dan para guru bertugas melibatkan diri secara serius dalam membentuk kesadaran dan sikap politik peserta didik mereka.KATA KUNCI: Tindakan Pemberian Suara; Guru-guru; Pemilihan Umum Daerah; Senator dan Daftar Partai; Transformasi Sosial-Politik.Â Â About the Authors: Prof. Dr. Agnes S. Reyes and Prof. Dr. Judith R. Garcia are the Lecturers at the PNU (Philippine Normal University) in North Luzon, Aurora, Alicia, Isabela, the Philippines. For academic interests, the authors are able to be contacted via e-mail at: cardona.rs@pnu.edu.phHow to cite this article? Reyes, Agnes S. & Judith R. Garcia. (2015). âVoting Behavior of Teachers in North Philippines and its Implication to Educationâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.3(2), September, pp.205-216. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808.Chronicle of the article: Accepted (July 31, 2015); Revised (August 30, 2015); and Published (September 30, 2015).